Pengetahuan Dan Sikap Orang Banjar Mengenai Produk Farmasi Bersertifikasi Halal - Akhmad Jamaluddin Fikri; Anwar Hafidzi; M. Hanafiah (Sharia Journal and Education Center Publishing, 2023)
Abstract This study discusses the knowledge and attitudes of the people of Banjarmasin about halal-certified pharmaceutical products. The halal status of pharmaceutical products is in the spotlight because the Product Halal Guarantee Act requires halal certification. In the field, many drugs are unclear about their halal status, perhaps due to a lack of knowledge and public attention to this matter. This research is a field study of the knowledge and attitudes of the Banajarmasin community, with a phenomenological approach that is analyzed qualitatively descriptive. Data collection techniques using interviews. The conclusion of this study is that the level of knowledge of the banjar people regarding halal certification is high but the attitude of the banjar people regarding halal certification is low because they do not pay attention to halal-certified products when buying a medicine. Keywords: Halal certificate, Knowledge, Attitude Abstrak Penelitian ini membahas tentang pengetahuan dan siakap masyarakat Banjarmasin tentang produk farmasi bersertifikasi halal. Status kehalalan produk farmasi menjadi sorotan karena Undang-Undang Jaminan Halal Produk mengharuskan sertifikasi halal. Di lapangan, banyak obat yang belum jelas kehalalannya, mungkin karena kurangnya pengetahuan dan perhatian masyarakat terhadap hal tersebut.. Penelitian ini bersifat kajian lapangan terhadap pengetahuan dan sikap masyarakat Banajarmasin, dengan pendekatan fenomenologi yang dianalisis secara kualitatif deskriptif. Teknik pengambilan data menggunakan wawancara. Kesimpulan penelitian ini adalah tingkat pengetahuan orang banjar mengenai sertifikasi halal terbilang tinggi tetapi sikap orang banjar mengenai sertifikasi halal terbilang rendah karena mereka ketika membeli suatu obat tidak memperhatikan produk yang bersertifikasi halalnya. Kata Kunci: Sertifikat halal, Pengetahuan, Sikap